2017
DOI: 10.1038/srep41231
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic interplay between ceramide and insulin resistance

Abstract: Recent research adds to a growing body of literature on the essential role of ceramides in glucose homeostasis and insulin signaling, while the mechanistic interplay between various components of ceramide metabolism remains to be quantified. We present an extended model of C16:0 ceramide production through both the de novo synthesis and the salvage pathways. We verify our model with a combination of published models and independent experimental data. In silico experiments of the behavior of ceramide and relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
(62 reference statements)
1
31
0
Order By: Relevance
“…Thus ceramide is not considered in the pathogenesis of hepatic IR or mechanism of RES protective effect in the model used in the current study. 21 In this study, HFD-fed rats had stable plasma glucose levels but higher fasting insulin levels, suggesting the development of IR. These results have also been shown by other authors using the same animal model.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Thus ceramide is not considered in the pathogenesis of hepatic IR or mechanism of RES protective effect in the model used in the current study. 21 In this study, HFD-fed rats had stable plasma glucose levels but higher fasting insulin levels, suggesting the development of IR. These results have also been shown by other authors using the same animal model.…”
Section: Discussionsupporting
confidence: 48%
“…Authors who have used the 3‐day HFD animal model to investigate hepatic IR found no alteration in ceramide content in these rodents. Thus ceramide is not considered in the pathogenesis of hepatic IR or mechanism of RES protective effect in the model used in the current study …”
Section: Discussionmentioning
confidence: 99%
“…This problem is often formulated in the form of least squares, as in models related to diabetes [10,19,20], biological pathways [21][22][23][24], and pharmacokinetics/pharmacodynamics [25,26]. Least squares problems may arise in statistical regression as well [27][28][29][30][31][32].…”
Section: Least Squares Methodsmentioning
confidence: 99%
“…During the last two decades, different models have been proposed to mechanistically explore different aspects of the sphingolipid metabolism (Alvarez‐Vasquez et al, ; Gupta et al, ; Kaddi, Niesner, et al, ; Kaddi, Reali et al, ; Reali et al, ; Wronowska, Charzyńska, Nienałtowski, & Gambin, ). Here, we analyze two models that have been simulated using three different approaches, and each approach has led to different discoveries.…”
Section: A Simulation Test‐case In Computational System Biology: the mentioning
confidence: 99%
“…In literature, different models have been devoted to studying sphingolipid metabolism and in particular of ceramide. Here, we analyze how the use of three simulation algorithms have supported the different findings on two of these models (Gupta, Maurya, Merrill, Glass, & Subramaniam, 2011;Reali, Morine, et al, 2017;Thanh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%